Knowledge Organization and innovations in disasters victims identification - Gonçalves Teixeira, Rodrigo; de Sales, Rodrigo (Advanced Notes in Information Science, 2023)
Disasters have always generated great social interest for several factors linked to these phenomena. Within the themes related to these episodes, disaster victim identification (DVI) is one of the main focuses of studies. The scope of this article is to present links between Information Science and the DVI theme. Through a qualitative study using the bibliographic review technique, examples of case studies were sought in the literature in which innovation concepts were approached, as well as knowledge organization. The DVI response is a management process in which several activities are developed until the final product is obtained, which is the identification. As a process, there are opportunities for innovation in the phases that compose it and the need to register knowledge so that it can be recovered and debated. The debriefing provided in Interpol’s DVI Guide, called “Phase 5”, is a crucial and necessary step for maximum expertise gain in preparation for future events. Opportunities arise in this phase to improve existing protocols for the other four phases of the DVI process: local, antemortem, post-mortem, and reconciliation.